APPROACH TOWARDS SACROCOCCYGEAL FISTULA: A PROSPECTIVE CLINICAL AND COMPETITIVE INTERPRETATION (AYUSHDHARA, 2021)
Background: Sacrococcygeal fistula, also known as Pilonidal sinus is an acute or chronic infection in the subcutaneous fatty tissue, mainly in the natal cleft. The condition, though not life threatening, is socially embarrassing and adversely affects the quality of life of patients. In Ayurvedic literature Sacrococcygeal fistula is better correlated and treated as Nadi Vrana. Acharya Sushruta had explained Para-surgical procedure with the intervention of medicated Seton (Kshara Sutra) as one of the treatment modalities. The ideal method of treatment of Sacrococcygeal fistula should be effective with a low recurrence rate, short hospital stay and economical.Aim: This study is an attempt to evaluate the efficacy of Arka Ksharasutra in the management of Sacrococcygeal fistula.Methodology: A total no. of 10 patients having signs and symptoms of Sacrococcygeal fistula were selected for Arka Ksharasutra ligation under local anesthesia and the Seton was changed every week during the entire treatment period.Results: In this study all the patients i.e.,100% were males with age between 25-35 years. The length of initial track was 3.6 to 5.5 cm and average Unit Cutting Time was 7.23 days/cm in previously non-operated cases and 11.26 days/cm in previously operated cases, average being 8.2days/cm. There was no post-operative complication and recurrence even after 3 months of follow-up.Conclusion: Arka Ksharasutra is laced with anti-bacterial, anti-fungal, bactericidal and anti- inflammatory properties which minimizes the use of antibiotics and also demolished the recurrence of symptoms.